A STUDY ON INDONESIAN TEACHERS’ USE OF TECHNOLOGY IN ENGLISH LANGUAGE TEACHING - Isry Laila Syathroh; Bachrudin - Musthafa; Pupung - Purnawarman (Journal Of Educational Experts (JEE), 2020)
Since 1960, technology has been used as one of educational tools to help teachers in teaching learning process. In the context of foreign language teaching, technology is utilized for various reasons and purposes. A questionnaire was distributed to 150 English as foreign Language (EFL) teachers in West Java to investigate the use of technology in their EFL classroom. Specifically, this paper reports the type of technology which teachers usually use in teaching English and also elaborate the reasons why teachers apply technology in their classrooms. Finally, this paper explores teachers’ attitudes on the use of technology in language teaching.